Potential Enhancement in The Nutritional Value of Local Agro-Waste Through Cultivation of Pink Oyster Mushroom (Pleurotus djamor) - Amelia Lulu Rosalin Hutabarat; Wenni Meika Lestari; Anton Kuswoyo; Abdul Muta Ali; I. Sari (Universitas Bengkulu, 2022)
The present study aimed to examine the effect of locally available agro-industrial wastes on the growth and productivity of pink oyster mushrooms (Pleurotus djamor) and the potential use of substrates as animal feeding based on its compositional change following mushroom growth. A total of three substrate formulations labeled OPF (80% oil palm frond), CS (80% corn straw), and OPFCS (40% oil palm frond + 40% corn straw) were prepared. Aside from the earliest mycelium completion, pinhead formation, and fruiting bodies maturation, CS and OPFCS exhibit the best total yield, dry weight, and biological Efficiency. On the contrary, P. djamor grown in OPF resulted in the minimum in most of the parameters measured. Therefore, CS, single and in combination with OPF could be utilized as an alternative growing media for the cultivation of P. djamor. The analysis of chemical compositions showed that the growth of P. djamor significantly reduced the crude fiber (CF) and increased the crude protein (CP) content of the mycelium-treated substrate. In contrast, THE CP content of the spent is unchanged or relatively lower than that of the initial substrate. It can be concluded that compared to the spent, mycelium-treated substrate had higher values of being used for animal feeding.